Case series: Amniotic band sequence with craniofacial abnormalities. Issue 19 (13th August 2019) - Lies, Shelby; Beckwith, Terri; Mills, Janith; Butler, Lesley; Ezaki, Marybeth; Oishi, Scott
Abstract: Background: To objectively describe craniofacial, visual, and neurological features associated with amniotic band syndrome (ABS) and discuss likely associated multifactorial etiology. Methods: A retrospective review of patients identified with ABS and concomitant limb involvement and craniofacial features was conducted. The following data were collected from the patients' medical records: demographic information, past medical history including birth history, surgical history, previous clinic visits/physical exams, description of craniofacial features and ABS, family history, any noted obstetric complications, visceral features, visual features, craniofacial features, intracranial features, neurological symptoms, developmental features, diagnostic tests (including radiographs, IQ testing, EEG findings, chromosomes), photographs, and treatment history. Results: Seven patients were included in the final cohort, all of whom had a cleft lip with six having both cleft lip and palate. Other craniofacial abnormalities seen were facial clefts which were vertical oblique in nature, tear duct involvement, cranial deformities that required surgical correction with cranial reconstruction, recorded hypertelorism with vision and gaze abnormalities, coloboma, lagopthalmos and optic never dysplasia. Conclusions: This case series presents seven children with craniofacial involvement associated with amniotic band sequence and attempts to categorize the salient dysmorphology and neurocognitive development. Major craniofacial anomalies in patients with ABS is a rare clinical finding that cannot be completely explained on the basis of premature amniotic layer disruption alone. This study supports that the dysmorphology seen in cases of ABS with craniofacial involvement is complex and most likely multifactorial. Level of Evidence: IV Case Series.